2017
DOI: 10.1097/tp.0000000000001329
|View full text |Cite
|
Sign up to set email alerts
|

Twelve-Week Rifapentine Plus Isoniazid Versus 9-Month Isoniazid for the Treatment of Latent Tuberculosis in Renal Transplant Candidates

Abstract: Twelve-week RPT/INH appears to be an excellent choice for LTBI in RTC. It has a higher treatment completion rate and causes less transaminase elevations, and weekly reminders may be an alternative when direct observed therapy is not feasible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
58
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(59 citation statements)
references
References 16 publications
0
58
1
Order By: Relevance
“…A total of 23 publications related to RCTs and 55 related to nonrandomized studies were included. A flow diagram documenting the process of study selection is provided in Figure .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 23 publications related to RCTs and 55 related to nonrandomized studies were included. A flow diagram documenting the process of study selection is provided in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…Data from nonrandomized studies found that the highest median rate of withdrawals from adverse events was associated with INH‐6 (median 5.8%, range 2.3%‐24.5%; 9 studies), followed by INH/RPT‐3 (median 4.3%, range 1.3%‐8.4%; 7 studies), INH‐9 (median 2.6%, range 0.4%‐26.8%; 13 studies), INH/RMP 3‐4 (median 1.8%, range 0.5%‐5.1%; 4 studies), and RMP 3‐4 (median 0%, range 0%‐5.2%; 6 studies).…”
Section: Resultsmentioning
confidence: 99%
“…Our study is limited by the small number of cases, retrospective design, and lack of control group. Completion rates with RPT/INH are excellent [2] …”
mentioning
confidence: 99%
“…Rifapentine/isoniazid (RPT/INH) administered for 12 weeks is one of the first-line treatments for LTBI [1], and we have recently showed that it is associated with higher completion rates than INH monotherapy for 9 months [2].One theoretical concern in RTC is that RPT can decrease the efficacy of certain antihypertensive drugs (AHD) through the induction of cytochrome P (CYP) 3A4-CYP2C9 [3]. Namely, RPT can accelerate the metabolism of beta-and/or alpha-blockers, calcium channel blockers, and angiotensin receptor blockers [3,4].…”
mentioning
confidence: 99%
See 1 more Smart Citation